2014
DOI: 10.1002/mc.22197
|View full text |Cite
|
Sign up to set email alerts
|

GOLPH3 promotes glioblastoma cell migration and invasion via the mTOR‐YB1 pathway in vitro

Abstract: The identification of genes involved in carcinogenesis and tumor progression is of great interest, since these genes might be possible as candidates for new tumor targeted therapy strategies. Our previous study shows that Golgi phosphoprotein 3 (GOLPH3) is involved in glioma cell migration and invasion, the critical characteristics of malignant gliomas. In this study, we explored the mechanism of GOLPH3 affecting cell migration and invasion and found that GOLPH3 promotes glioblastoma (GBM) cell migration and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 36 publications
3
52
0
Order By: Relevance
“…Notably, GOLPH3 shRNA did not affect the protein level of GOLPH3 paralogue GOLPH3L [37] (sFig. 1B-1D) and could be rescued by GOLPH3 Res (shRNA-resistant mutant of GOLPH3), indicating the specificity of GOLPH3 shRNA [19,21]. Furthermore, the high down-regulation efficiency of GOLPH3 shRNA was also confirmed by immunofluoresence assay (see online suppl.…”
Section: Golph3 Promotes the Proliferation Of Human Glioma Cellsmentioning
confidence: 79%
See 1 more Smart Citation
“…Notably, GOLPH3 shRNA did not affect the protein level of GOLPH3 paralogue GOLPH3L [37] (sFig. 1B-1D) and could be rescued by GOLPH3 Res (shRNA-resistant mutant of GOLPH3), indicating the specificity of GOLPH3 shRNA [19,21]. Furthermore, the high down-regulation efficiency of GOLPH3 shRNA was also confirmed by immunofluoresence assay (see online suppl.…”
Section: Golph3 Promotes the Proliferation Of Human Glioma Cellsmentioning
confidence: 79%
“…Studies about the mechanism of GOLPH3 in cancer biology are mainly focused on the following signal pathways, such as mTOR-YB1, GSK3β-FOXO1 and AKT-mTOR, but rarely attach importance to its biological roles of golgi trafficking, receptor recycling and glycosylation in cancers [12,17,19]. It is reported that GOLPH3 interacts with and mediates the golgi localization of POMGnT1 [42], a mammalian glycosyltransferase, which promotes glioblastoma progression [43].…”
Section: Discussionmentioning
confidence: 99%
“…Unless otherwise indicated, drug concentrations were as follows: vorinostat (2μM), romidepsin (1nM), panobinostat (20nM), sapanisertib (200nM for all cell lines except 90-8TLs, where sapanisertib was used at 100nM), auranofin (750nM), buthionine sulfoximine (200 μM). The concentration of sapanisertib (200nM) was chosen based on previously published studies (23,56,57). 100nM was used in 90-8TLs for historical reasons but 200nM produces the same results.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence of transformation by overexpression of GOLPH3 has been reported in MDA-MB-231 and MCF7 breast cancer cell lines (911), and U251 and U87 glioblastoma cell lines (12, 13). Frequent overexpression of GOLPH3 and correlation with poor prognosis have been reported in multiple tumor types including 58–72% of non-small cell lung cancers (14, 15), 52% of breast cancers (11), 70% of prostate cancers (16), 73% of pancreatic ductal adenocarcinomas (17), 65% of hepatocellular carcinomas (18, 19), 55–58% of gastric cancers (20, 21), 53% of renal cell carcinomas (22), 41–53% of glioblastomas (12, 23, 24), 49% of esophageal squamous carcinomas (25), and 45% of ovarian carcinomas (26, 27). Overexpression of GOLPH3 occurs frequently in rhabdomyosarcoma, and knockdown of GOLPH3 in rhabdomyosarcoma cell lines impairs cell proliferation (28).…”
Section: Golph3 Is An Oncogenementioning
confidence: 91%